2013
DOI: 10.1021/am400063k
|View full text |Cite
|
Sign up to set email alerts
|

Ratiometric, Reversible, and Parts per Billion Level Detection of Multiple Toxic Transition Metal Ions Using a Single Probe in Micellar Media

Abstract: We present the selective sensing of multiple transition metal ions in water using a synthetic single probe. The probe is made up of pyrene and pyridine as signaling and interacting moiety, respectively. The sensor showed different responses toward metal ions just by varying the medium of detection. In organic solvent (acetonitrile), the probe showed selective detection of Hg2+ ion. In water, the fluorescence quenching was observed with three metal ions, Cu2+, Hg2+, and Ni2+. Further, just by varying the surfac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
60
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 94 publications
(61 citation statements)
references
References 60 publications
1
60
0
Order By: Relevance
“…Combining pyrene and pyridine together as signaling and interacting units respectively, Kumari et al [74] reported a single probe 45 for differential sensing of more than one transition metal ions at parts per billion levels. The probe could recognize Hg 2+ in acetonitrile as well as in neutral micellar medium (Brij-58) by showing Fig.…”
Section: Dual-channel Sensorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Combining pyrene and pyridine together as signaling and interacting units respectively, Kumari et al [74] reported a single probe 45 for differential sensing of more than one transition metal ions at parts per billion levels. The probe could recognize Hg 2+ in acetonitrile as well as in neutral micellar medium (Brij-58) by showing Fig.…”
Section: Dual-channel Sensorsmentioning
confidence: 99%
“…46. Structure of probe 45 which shows dual-channel sensing behavior toward Hg 2+ , Cu 2+ and Ni 2+ ions in differently charged micellar medium [74]. fluorescence quenching behavior.…”
Section: Dual-channel Sensorsmentioning
confidence: 99%
“…Moreover, we also studied the photophysical behavior of 3 and its selectivity for CN -in the neutral, cationic and anionic surfactant micellar medium. In fact, micelles in a simple model, mimic the membranes of biosystems [47,48] and is expected to modify and/or improve photophysical/photochemical processes due to a change in the micropolarity, surface charges and rigidity inside the micellar microenvironments [45,46]. Interestingly, when the emission spectra were acquired in the presence of SDS, CTAB and Triton (concentration above CMC) probe 3 showed relatively better emission behavior in Triton and also could able to detect CN -selectively, through enhanced emission (Supporting information; Figure S36).…”
Section: Detection Of Cn -In Real Contaminated Water Samples and Micementioning
confidence: 99%
“…Today, different types of fluorescent receptors are known for the sensing of Hg 2+ and Cu 2+ [15][16][17][18][19][20]. However, they often show fluorescence quenching (turn-off) response.…”
Section: Introductionmentioning
confidence: 99%